2021
DOI: 10.1177/10760296211026385
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Coagulation Indicators and Coagulant Agents With 30-Day Mortality of Critical Diabetics

Abstract: Diabetes, regarded as a global health concerned disease, was focused by the World Health Organization (WHO). Patients with diabetes may have a hypercoagulable and hypo-fibrinolysis state. There is lots of research about cardiovascular effects on diabetes patients, but less about the coagulation system. This study is designed to investigate the relationship between coagulation indicators and 30-day mortality of critical diabetes patients. In this retrospective, single-center study, we included adult patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The pathophysiological mechanism of DFU is still debated. Previous studies have identified diabetic foot as one of the serious complications caused by pathophysiological changes such as inflammation, endothelial dysfunction, and blood coagulation imbalance (33). The presence of immune cells in an environment of chronic hyperglycemia and hypertriglyceridemia caused chronic immune system disorders and impaired responses to acute infections and sepsis in patients with DFU.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiological mechanism of DFU is still debated. Previous studies have identified diabetic foot as one of the serious complications caused by pathophysiological changes such as inflammation, endothelial dysfunction, and blood coagulation imbalance (33). The presence of immune cells in an environment of chronic hyperglycemia and hypertriglyceridemia caused chronic immune system disorders and impaired responses to acute infections and sepsis in patients with DFU.…”
Section: Discussionmentioning
confidence: 99%